The development and evaluation of interdisciplinary STEM, sustainability, and management curriculum. Issue 2 (July 2022) - Craig, Christopher A.; Petrun Sayers, Elizabeth L.; Gilbertz, Susan; Karabas, Ismail
Abstract: There is an increasing need in the workforce for STEM and sustainability literate graduates. In practice, however, it is difficult to enact interdisciplinary STEM and sustainability curriculum, particularly in business disciplines. To address this gap, we designed, developed, implemented, and evaluated an interdisciplinary STEM, sustainability, and management course called Applied Organizational Sustainability using the ADDIE (analyze, design, develop, implement, evaluate) model for instructional design. We used a robust multi-method evaluation that includes pre-/post-tests and treatment/control groups to longitudinally assess changes in student sustainability knowledge. Quantitative results indicate significant improvement in three of the four sustainability knowledge measures for treatment students but not for control students. Qualitative results from a focus group indicate that (1) content was new to business and management students, (2) students found the content to be relevant to employment, and (3) students viewed the content as valuable to university curriculum. These results provide research-based support for the adaptation and expansion of interdisciplinary STEM and sustainability curriculum in higher education, including adaptation of Applied Organizational Sustainability, its modules, and/or its assignments. Highlights: There is a need for a STEM and sustainability literate workforce. However, interdisciplinary STEM, sustainability, and management curriculum is rare. Addressing the gap, we created and evaluated an interdisciplinary course. Curriculum was evaluated using pre-/post-tests and treatment/control groups. Sustainability knowledge improved for treatment but not control group students.